Letter from Jane Tolmach to Marcia Herman and Mary Aidlin - Jane Tolmach::::::
This two-page letter is from Jane Tolmach to Marcia Herman and Mary Aidlin of the Politics Committee of Women For in Beverly Hills regarding her candidacy for the 36th Assembly District. She encloses campaign materials outlining her background and qualifications and emphasizes her substantial record of achievement in government and civic affairs, noting that she is both the only woman and, in her view, the most qualified candidate in the race. Tolmach identifies key campaign issues, beginning with tax reform, advocating more progressive taxation, elimination of certain corporate tax exemptions, and property tax reform to better support local government and schools. She also highlights political reform, expressing support for Proposition 9 and calling for greater openness and responsiveness in government. Additional priorities include conservation—supporting coastal protection and mass transit initiatives—and social welfare, emphasizing humane living standards, expanded opportunity, and effective government programs to meet unmet social needs.